1582 Radiolucent Foreign Bodies Presenting As IBD- The Case of An Ingested Plastic Straw Disguising as Crohn's Disease. (12th October 2021) - Wadham, B; Connolly, T; Satchidanand, R
Abstract: Ingested foreign bodies (FBs) occur most commonly in children or adults with impaired neurological function. Overall, 80% are thought to pass spontaneously in the faeces, with around 20% requiring endoscopy and less than 1% requiring surgical intervention. 'Missed' gastro-intestinal FBs are rare and often due to the lack of an obtainable history in patients with communication difficulties. We present the unusual case of a 27-year-old female with severe learning difficulties and a complex surgical history who presented with a 2-year history of increasing abdominal discomfort due to a 'missed' FB. Four CT scans had misdiagnosed Crohn's disease and the patient was due to commence immunosuppression when she developed a small bowel perforation. This was managed conservatively and follow-up imaging with a CT with oral contrast detected the FB in the ileum. The patient underwent a laparotomy with resection of a 26cm segment of ileum containing a plastic straw. Post-operatively she recovered uneventfully and is now symptom free with no evidence of IBD on histology. This case highlights the value of oral contrast enhancement imaging in patients who don't fit a 'classical' inflammatory bowel disease presentation.